2011
DOI: 10.1038/leu.2011.104
|View full text |Cite
|
Sign up to set email alerts
|

Importance of c-kit mutation detection method sensitivity in prognostic analyses of t(8;21)(q22;q22) acute myeloid leukemia

Abstract: Recently, c-kit mutations have been reported as a novel adverse prognostic factor of acute myeloid leukemia with t(8;21)(q22;q22) translocation (t(8;21) AML). However, much remains unclear about its clinical significance. In this study, we developed a highly sensitive mutation detection method known as mutation-biased PCR (MB-PCR) and investigated the relationship between c-kit mutations and prognosis. When c-kit mutations were analyzed for 26 cases of t(8;21) AML using the direct sequence (DS) and MB-PCR, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…Thus, Ding and coworkers sequenced the primary leukemia and relapse genomes from eight AML patients allowing to define two major clonal evolution patterns during AML relapse: (i) the clonal evolution of the leukemias is related to the founding clone through the gain of mutations, allowing its transformation into the relapse clone; (ii) the clonal evolution of the tumor is dependent upon a subclone minoritary at diagnosis, surviving to the induction therapy, acquiring new mutations, and expanding at relapse [18]. In t(8; 21) AMLs, a minoritary subpopulation of leukemia cells that harbored c-kit mutations at diagnosis becomes dominant at relapse [19]. Furthermore, a study carried out on a small subset of CD34 + AML patients, mostly with normal karyotype, showed that these AMLs harbor an oligoclonal immature compartment at presentation, with the presence of a minor subpopulation in initial diagnosis samples, but dominating the bulk leukemic blasts at relapse [20].…”
Section: The Molecular Classification Of Acute Myeloid Leukemiasmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Ding and coworkers sequenced the primary leukemia and relapse genomes from eight AML patients allowing to define two major clonal evolution patterns during AML relapse: (i) the clonal evolution of the leukemias is related to the founding clone through the gain of mutations, allowing its transformation into the relapse clone; (ii) the clonal evolution of the tumor is dependent upon a subclone minoritary at diagnosis, surviving to the induction therapy, acquiring new mutations, and expanding at relapse [18]. In t(8; 21) AMLs, a minoritary subpopulation of leukemia cells that harbored c-kit mutations at diagnosis becomes dominant at relapse [19]. Furthermore, a study carried out on a small subset of CD34 + AML patients, mostly with normal karyotype, showed that these AMLs harbor an oligoclonal immature compartment at presentation, with the presence of a minor subpopulation in initial diagnosis samples, but dominating the bulk leukemic blasts at relapse [20].…”
Section: The Molecular Classification Of Acute Myeloid Leukemiasmentioning
confidence: 99%
“…The purified residual hematopoietic stem cells were screened for the presence of leukemia-associated mutations and were found to possess some leukemia-associated mutations, such as TET2, NPM1, and SMC1A; however, the FLT3-ITD mutation was not found in these residual hematopoietic stem cells [23]. Considering the total number of mutations (51 mutations) present in leukemic cells, a large part of them (32 mutations) were detectable in nonleukemic hematopoietic stem cells [19]. According to these findings, the residual hematopoietic stem cells have been defined as “preleukemic” stem cells [23].…”
Section: The Molecular Classification Of Acute Myeloid Leukemiasmentioning
confidence: 99%
“…The ligand for KIT is stem cell factor (SCF) and binding of SCF to c-kit induces activation of downstream signaling pathways that are involved in mediating growth and survival signals within the cell including the P13K-AKT-mTOR pathway and the RAS-RAF-MEK-ERK pathway. KIT has been implicated in the pathogenesis of several cancers including acute myeloid leukemia and gastrointestinal stromal tumors (GIST) [46-49]. Unlike in GIST where c-kit mutations tend to be deletions or insertions in exon 11, c-kit mutations in melanoma occur at multiple sites along the gene including both the juxta-membrane domain at exon 11 and exon 13 and the kinase domain at exon 17 and are usually point mutations that do not correlate with KIT copy number or CD117 expression [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…Although the inhibition of the mutated ABL was efficacious to the CML, a substantial number of patients had failed to respond to the ABL inhibitors by developing drug resistance [52]. Src’s pathway [54] and c-kit’s mutation [55] were reported to contribute significantly to the drug resistance, and were the key adverse prognostic and predictive prognosis factors for leukemia [54,55]. Thus, the multi-target drugs inhibiting ABL together with Src or c-Kit were expected to counteract drug resistance of the existing ABL inhibitors.…”
Section: Resultsmentioning
confidence: 99%